Financial Counseling: Financial Ethics and Consumer Psychology to Reduce the Risk of Online Loans for Kupang Students: Financial Counseling: Financial Ethics and Consumer Psychology to Reduce the Risk of Online Loans for Kupang Students - Messakh, Merling; Ufi , Delsylia Tresnawaty (Institut Agama Kristen Negeri Kupang, 2024)
This study explores the role of financial counseling that integrates money ethics and consumer psychology in mitigating the risk of online loan use by university students in Kupang City. This study is motivated by the increasing use of online loans which often leads to negative impacts, including financial problems and psychological distress. Using a qualitative approach, data was collected through in-depth interviews with university students and analysis of related literature. The results showed that an understanding of money ethics and psychological awareness in financial management have a significant impact on reducing the risks associated with the use of online loans. Financial counseling that focuses on the integration of money ethics and consumer psychology proved effective in helping university students manage their finances more wisely/while improving their financial resilience. Policy recommendations resulting from this research include the development of a campus-based financial counseling program tailored to students' needs, as well as the strengthening of financial literacy and ethics in the higher education curriculum. This research contributes to the development of contextually relevant risk mitigation strategies